2020
DOI: 10.3390/genes11050494
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity, Population Structure, and Signature of Selection in Five Chinese Native Sheep Breeds Adapted to Extreme Environments

Abstract: Through long term natural and artificial selection, domestic sheep (Ovis aries) have become adapted to a diverse range of agro-ecological environments and display multiple phenotypic traits. Characterization of diversity and selection signature is essential for genetic improvement, understanding of environmental adaptation, as well as utilization and conservation of sheep genetic resources. Here, we aimed to assess genomic diversity, population structure, and genomic selection among five Chinese native sheep b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Therefore, it is beneficial to consider our results in historical demographic context of Chinese sheep population. This finding is in line with our previous studies of genomic diversity, population structure and selection signature, in which we observed that principal component and admixture analysis clustered population corresponding to their geographical distribution and breeding history [ 45 ]. In general, the increase of the estimated N e value across five sheep breeds generations ago suggest that these animals can ensure viability within breeds in breeding programs [ 58 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, it is beneficial to consider our results in historical demographic context of Chinese sheep population. This finding is in line with our previous studies of genomic diversity, population structure and selection signature, in which we observed that principal component and admixture analysis clustered population corresponding to their geographical distribution and breeding history [ 45 ]. In general, the increase of the estimated N e value across five sheep breeds generations ago suggest that these animals can ensure viability within breeds in breeding programs [ 58 ].…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, we revealed the genomic diversity, population structure and selection signature characteristics of five sheep populations in China [ 45 ]. Here, we extended our analysis using runs of homozygosity, LD and N e as useful tools for detecting genomic relatedness, providing population assessment historical information over time and predicting underlying genome architecture [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of multiple methods reduces the chance of false positive results. In this study, there were many overlapping regions identified between at least two approaches ( Supplementary Table 5 ), which provides stronger evidence of selection for specific traits ( Hohenlohe et al, 2010 ; Oleksyk et al, 2010 ; Abied et al, 2020 ). It is worth mentioning that the use of different methods can result in the identification of different regions ( Fariello et al, 2013 ), as methods might be based on different source of information (e.g., single-SNP allele frequency or haplotype structure).…”
Section: Discussionmentioning
confidence: 64%
“…Local sheep breeds traditionally raised under extreme environments are an excellent model for studying genetic adaptation [ 4 ]. Under these conditions, selective breeding for improved (re)productive performance is limited or non-existent, leaving natural selection as the primary evolutionary acting mechanism.…”
Section: Introductionmentioning
confidence: 99%